2003
DOI: 10.1124/jpet.103.057836
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Molecular Recognition of Psychostimulants by Human andDrosophilaSerotonin Transporters

Abstract: In this study, human embryonic kidney (HEK)-293 cells stably expressing human, Drosophila, or a chimeric serotonin (5-hydroxytryptamine, 5-HT) transporter (hSERT, dSERT, , respectively) were used to explore the ability of two libraries of structurally distinct psychostimulants to inhibit 5-HT uptake. One library consisted of 3-phenyltropane analogs, whereas the second library consisted of several substituted amphetamines. hSERT exhibited a lower K i value for all the compounds in both libraries compared with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…1,2 SERTs are targets of antidepressants and substances of abuse like cocaine and 3,4methyl-dioxy-methamphetamine, commonly known as "Ecstasy." 3 Hydropathy analyses initially suggested that SERTs are integral membrane proteins with 12 α-helices. 2,4,5 Sitedirected mutagenesis and substituted cysteine accessibility method (SCAM) experiments on putative transmembrane TMs and loops have supported this proposal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 SERTs are targets of antidepressants and substances of abuse like cocaine and 3,4methyl-dioxy-methamphetamine, commonly known as "Ecstasy." 3 Hydropathy analyses initially suggested that SERTs are integral membrane proteins with 12 α-helices. 2,4,5 Sitedirected mutagenesis and substituted cysteine accessibility method (SCAM) experiments on putative transmembrane TMs and loops have supported this proposal.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified amino acid sequence differences among SERT species that confer alternate specificities for substrates and inhibitors. 3,[12][13][14] Barker et al 15 used human SERT (hSERT) and Drosophila SERT (dSERT) chimeras to implicate Y95 in forming part of the recognition site for citalopram and mazindol, two biogenic amine reuptake inhibitors. Adkins et al 14 used the same approach to show the Y95F hSERT mutant exhibits dSERT-like recognition of N-isopropyl tryptamine.…”
Section: Introductionmentioning
confidence: 99%
“…As members of the sodium and chloride‐dependent neurotransmitter transporter gene family, serotonin (5‐HT) transporters (SERTs) carry out the uptake of 5‐HT across plasma membranes in the central nervous system, peripheral nervous system, placenta, platelets, and pulmonary system 1, 2. SERTs are targets of antidepressants and substances of abuse like cocaine and 3,4‐methyldioxy‐methamphetamine, commonly known as “Ecstasy.”3 Hydropathy analyses initially suggested that SERTs are integral membrane proteins with 12 α‐helices 2, 4, 5. Site‐directed mutagenesis and substituted cysteine accessibility method (SCAM) experiments on putative transmembrane TMs and loops have supported this proposal 6–10…”
Section: Introductionmentioning
confidence: 99%
“…implicated I172 and I176 in substrate and inhibitor binding through protection of transporter function from inactivation by methanethiosulfonate reagents (MTS) in cysteine mutants of these residues. Several studies have identified amino acid sequence differences among SERT species that confer alternate specificities for substrates and inhibitors 3, 12–14. Barker et al 15.…”
Section: Introductionmentioning
confidence: 99%
“…Class 2 GPCRs in this category include the CGRP 1 (Hershey et al, 2005;Mallee et al, 2002), glucagon-like peptide 1 (GLP 1 ) receptor (Tibaduiza et al, 2001) and VIP/PACAP receptor VPAC 1 (Couvineau et al, 1996). The vanilloid receptor TRPV 1 (Valenzano and Sun, 2004), serotonin transporter SERT (Barker et al, 1994;Roman et al, 2004) and the kinase porphobilinogen synthase (Kervinen et al, 2001) are examples of ion channels, transporters and kinases, respectively, that show species differences in pharmacology. Several of the targets described above have been implicated in pain transmission/sensitization/modulation.…”
mentioning
confidence: 99%